Planning and Enabling Learning in the Lifelong Learning Sector - Gravells, Ann.; Simpson, Susan, 1958- (Exeter : Learning Matters, 2008)
Planning and Enabling Learning is a core unit of the new teaching qualifications, and this title fully addresses all the required learning outcomes and content of that unit, specifically targeted at learners taking the Certificate or Diploma in Teaching in the Lifelong Learning Sector (CTTLS or DTTLS).
Formerly CIP.
Includes bibliographical references and index.
Keywords: Continuing education; Continuing education -- Planning